Verification of Gamification Tools as an Acute Trend of Motivation Theory in the Context of Managing Advanced Organizations Based on Case-Method - E. U. Ganshina; I. L. Smirnova; S. P. Ivanova (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
According to traditional motivation methodology companies are considered successful in case they stimulate personnel for new organizational achievements and at the same time they do not have high staff turnover and optimize costs. B. Skinner, the founder of the concept of operant conditionality thought that there were only two tools that can cause modification of employee behavior, i.e. support and punishment. However, empiric research of company practice based on case-analysis show that the level of employee efforts aimed at production figures cannot always correspond to the level of reward both tangible and intangible. In B. Skinner’s concept there is a certain noncomprehended field, which requires additional study. The article came to the conclusion that there is not always a direct dependence between indicators of employee efforts and the level of reward, moreover game practices (gamification) are used in companies, where this correlation is not evident. The authors analyzed a number of today’s organizations in the context of introducing gamification tools to stimulate the efficient work of personnel with regard to cost optimization. Findings of the research can be used for further critical revision of traditional motivation methods in times of global digitalization and management transformation.